Double Outlet Right Ventricle with Pentalogy Physiology in Adult Women: A Case Report - Lakshmi, R.Vijaya; Yadav, Umesh; Gacchhadar, Pritam; Kumar, Vasant; Mandal, Jay (Medical Journal of Eastern Nepal, 2023)
Double right ventricle outlet (DORV) is a rare cardiac abnormality, especially in adult life. DORV is a rare and complex congenital heart disease that has a high rate of genetic anomalies and extracardiac pathologies. Echocardiography plays an important and cost-effective role in the diagnosis of complex congenital cardiac diseases and assists in surgical planning. Here, we present a case of 38 years old woman who came to our outpatient department with shortness of breath which was progressive during exertion but relief on rest. Clinical examination showed low oxygen saturation of 70% without clubbing of fingers and toes. Holosystolic murmur and diastolic regurgitant murmur were audible along the left Sternal border. Chest X-ray showed cardiomegaly and enlarged pulmonary trunks. Electrocardiography showed right axis deviation and biventricular hypertrophy. After the echocardiogram, it turned out she had DORV. The study emphasizes the role of echocardiography in evaluating DORV.